The role of social media marketing in enhancing vegetarian food literacy and shaping consumer purchase decisions - Nadya Sherwin (Jurnal Riset Manajemen dan Bisnis, 2025)
This study aims to determine and analyze the effect of social media on vegetarian food literacy, investigate the impact of vegetarian food literacy on purchasing decisions, and identify the components of the AISAS model that most effectively influence consumer purchasing decisions. This study involved 158 respondents. Respondents consisted of Generation Y and Z individuals in Palembang, selected using a purposive sampling quota technique. Data collection was carried out using an online questionnaire. SEM-PLS analysis in this study was employed to examine the direct impact of social media on vegetarian food literacy and consumer purchasing decisions, utilizing AISAS modeling. The results of this study indicate that social media has a significant and positive impact on consumers' attention, interest, and search behavior. The share factor is the most influential factor on consumer purchasing decisions and on vegetarian products. The influence provided by influencer testimonials and friends is considered the most effective in attracting other consumers to make a purchase. This can serve as a reference for vegetarian food businesses to identify the most effective marketing methods for influencing consumer purchasing decisions.